Os BRICS na perspectiva geopolítica: uma análise cientométrica de 2001 a 2010 - Prado, Marcos Aparecido Rodrigues do [UNESP] (2014)
The contemporary world has a geopolitical construction in which the emerging market countries have been highlighted in the conjunction of global power. In this configuration, a group of countries was organized and has strengthened its representation in the international scene. Brazil, Russia, India, China and South Africa are the countries that share the expectations of a global power characterized by multipolarity. The governments of the four first mentioned countries articulated the formalization of a geopolitical bloc with strategic relevance for action against the international scene. Thus, the BRICS bloc was formed as a political organization that seeks to promote consorted actions covering economic, social and strategic development. In 2001, the acronym was coined by the english economist Jim O'Neill English as a result of a study that showed the four most promising countries among emerging economies. In 2006 it was begun a process of political integration among the four countries. The success of periodic governmental summits that followed led to the formalization of the BRIC bloc in 2009. And in 2010, the group expanded with the accession of South Africa as a full member. Since then, the block became officially termed as BRICS. It is with interest in such a geopolitical construction that this study is based on scientometry to analyze the economic and social indicators and their correlations with indicators of scientific production. Thus, the research aims to survey and analyze the data on scientific publications indexed in Scopus basis of the four countries that make up the genuine BRICS group, Brazil, Russia, India and China. Also, the scope of the study comprises the presentation of the concepts and applications of indicators as well as the identification of relevant features of the geopolitical scenario and scientific context in which the BRICS are inserted. The method used was the comparative study between indicators raised...